Application of the Spectral Method to the Equation of Shallow Waters - Luna Valdez, Juan (2017)
In this work we study the system of shallow water equations in the Lagrangian form and obtain its analytical solution. We apply the spectral method in the numerical analysis of this system and it is shown that the propagation of shallow water waves do not depend on the medium in which it propagates.